Cost of early-stage mycosis fungoides treatments in Spain - Ortiz-Romero PL; Servitje O; Estrach MT; Izu-Belloso RM; Fernández-; Gallardo F; López-Martínez N; Pérez-Mitru A (Dove Medical Press, 2020)
Pablo Luis Ortiz-Romero,1 Octavio Servitje,2 María Teresa Estrach,3 Rosa María Izu-Belloso,4 Ricardo Fernández-de-Misa,5 Fernando Gallardo,6 Noemí López-Martínez,7 Alejandro Pérez-Mitru7 1Dermatology Department, Hospital 12 de Octubre, Institute I+12, Medical School, University Complutense, CIBERONC, Madrid, Spain; 2Dermatology Department, Hospital Universitari de Bellvitge, IDIBELL, L’Hospitalet de Llobregat, Barcelona, Spain; 3Dermatology Department, Hospital Clínic, IDIBAPS, Universitat de Barcelona, Barcelona, Spain; 4Dermatology Department, Hospital de Basurto, Bilbao, Spain; 5Department of Dermatology and Research Unit, Hospital Universitario Nuestra Señora de Candelaria, Santa Cruz de Tenerife, Spain; 6Dermatology Department, Parc de Salut Mar-Hospital del Mar, Barcelona, Spain; 7Oblikue Consulting, Barcelona, SpainCorrespondence: Alejandro Pérez-MitruOblikue Consulting, C/Comte D’urgell, 240, 2-D, Barcelona 08036, SpainTel +34 932 521 377Fax +34 937 379 984Email alejandro.perez@oblikue.comAim: To identify the most common therapeutic options for the treatment of early-stage mycosis fungoides in Spain, quantify their associated healthcare resource use and costs.Methods: After reviewing the literature, a panel of 6 Spanish clinical dermatologists validated the treatments and healthcare resource use through a structured questionnaire. Individual responses were collected, analyzed and presented into a face-to-face meeting in order to reach a consensus. Cost categories considered were: drug acquisition and administration, photo/radiotherapy session and maintenance, clinical follow-up visits and laboratory tests. Costs were expressed in euros from 2018. The Spanish National Health System perspective was considered, taking into account direct health costs and time horizons of 1, 3 and 6 months.Results: Costs for the skin-directed treatments (SDT) assessed at 1, 3 and 6 months, were: Topical carmustine [€ 6,593.36, € 19,780.09 and € 27,592.78]; Phototherapy with psoralens and ultraviolet A light (PUVA) [€ 1,098.68, € 2,999.99 and € 3,187.60]; Narrow-band ultraviolet B phototherapy [€ 1,657.47, € 4,842.10 and € 4,842.10]; Total skin electron beam therapy (TSEBT) [€ 6,796.45, € 7,913.34 and € 7,913.34]. Cost for topical corticosteroids, being considered an adjuvant option, were € 17.16, € 51.49 and € 102.97. Costs for the assessed systemic treatments alone or in combination with SDT at 1, 3 and 6 months, were: Systemic retinoids [€ 2,026.03, € 5,206.63 and € 7,426.42]; Systemic retinoids + PUVA phototherapy [€ 3,066.50, € 8,271.26 and € 10,046.58]; Interferon alfa + PUVA phototherapy [€ 1,541.09, € 5,167.57 and € 6,404.55].Conclusion: According to the Spanish clinical practice, phototherapies in monotherapy were the treatments with the lowest associated costs regardless of the time horizon considered. TSEBT turned out as the treatment with the highest associated costs when considering 1 month. However, while considering 3 and 6 months the treatment with the highest associated costs was topical carmustine. The results of this analysis may provide critical information to measure the disease burden, to detect unmet medical needs and to advocate towards better treatments for this rare disease.Keywords: health care costs, health resources, mycosis fungoides, lymphoma, T-cell, cutaneous, surveys and questionnaires, Spain